Pengembangan Kompetensi Profesional Guru Bahasa Arab Melalui Penelitian Tindakan Kelas - Dina Indriana; Ahmad Arifin (Institut Agama Islam Negeri (IAIN) Metro, 2019)
The problem faced by teachers, primarily Arabic teachers is how to conduct classroom action research correctly. As for the condition of Madrasah Arabic language teachers in the Serang Regency, most do not have an understanding of this. Then the Department of Arabic Language FTK UIN Sultan Maulana Hasanuddin Banten implemented the Community Service Program to facilitate, bridge, and communicate various lecturer resources in the administration of Community Service. This type of dedication research is qualitative field research. The purpose of this activity that researchers often hear and get information about the difficulties of teachers when going to conduct classroom action research (CAR). Based on this, the researchers conducted community service, especially Madrasah Arabic language teachers in the Serang Regency for assistance, training, workshops, monitoring of the implementation of CAR. From the results of dedication shows that the learning process is still centered on the teacher (teacher center). Doing PTK by the teacher will be able to improve student learning outcomes. The researcher's recommendations are: 1) Arabic teachers should always conduct Classroom Action Research. 2) Adjusting the use of methods in learning with the material, learning objectives, and age of students. 3) The teacher can use learning media. 4) Teachers in teaching must feel happy and cheerful. 5) The use of the time that must be considered.